A ciência pode ser divertida: a emoção na mediação do conhecimento científico - Ana Paula Bossler da Costa (2009)
The present study is an attempt to pinpoint the emotional traits within three TV shows whose scope is the scientific knowledge from a discursive perspective. Two Brazilians productions called Globo Ecologia and Tudo é Possível, and one Portuguese production called ABCiencia were analyzed. After we took the audio transcriptions with chronological images descriptions, we wanted to recognize the constitutive elements in the communication deal of Shows investigated, identify the emotional traits, recover the voices in speeches of the subjects inside the scenes, recompose the thematic path unpacking of the subjects developed in each TV Show and examine the way of organization of leading speech. The educational purpose founded in the communication deal with the science how theme could justify the restrictive criterions for use of pathos in investigated TV Shows, considering that education and science are close areas for emotional states. The emotional repertoire founded is very similar in the three TV Shows, but Globo Ecologia Show uses this repertoire cautiously, although it demonstrates its high potential emotional. Although the play of TV presenters of three TVs Shows include to promote discursive mise en scéne of emotion, the emotional traits emerge from shared construction of interlocutors in scene, where the project of the voice of single subject dont guarantee the emotional meaning. The voice of professors appeared at speak of presenters in all TV Shows, confirming the educational character of this Shows. For the discursive course followed to thematic unpacking of Tudo é Possível and ABCiência TV Shows seems reproduce the scientific behavior sequence. The materials and the systems are showed to audience, they make the experiments and after that, there is discussion about results. Our research does notes to increase the audience of educational TV Shows that use the Science how thematic without forget learning possibility.